Variabilitas Spasio-Temporal Suhu Permukaan Laut di Sebagian Pesisir Kabupaten Banyuasin Propinsi Sumatera Selatan - Ningsih, Ellis Nurjuliasti; Agussalim, Andi; Barrus, Beta Susanto; Hartoni, Hartoni (Universitas Bengkulu, 2024)
ABSTRACT The coastal waters of Banyuasin are shallow marine waters directly connected to the Bangka Strait. The waters are drained by several large rivers and many small rivers, and the movement of water masses is influenced by tidal activity. Sea surface temperature as one of the physical factors of water is important to study considering its role can be used as an indicator of water quality, an indicator of the habitat of aquatic organisms, as well as a basis for studying climate change and several physical processes in the ocean, such as upwelling and fronts. This research aims to map the spatio-temporal distribution of sea surface temperature. The methods used are the remote sensing method and field surveys using image data in 2022–2023. The results showed that there are differences in the distribution of sea surface temperature both spatially and temporally. In the western season, also known as the western season, the temperature range is found in the range of 27.77–29.88 oC. In the first transitional season, the temperature range is 27.39–31.56 oC; the temperature distribution in the eastern season ranges from 30.13–33.89 oC; and the temperature range in the second transitional season is 24.47–30.37 oC. The highest sea surface temperatures occur in the eastern season, and these highest temperatures are lower in the western season. The spatial distribution of sea surface temperature is generally lower in coastal waters in the west and transition II seasons and higher in the transition I and east seasons. Keywords: sea surface temperature, remote sensing, Banyuasin coastal waters, Variability